Investasi Asing Langsung dan Ketimpangan Pendapatan di Indonesia (2015–2023): Implikasi bagi Kebijakan Pembangunan Inklusif - Regiana Revilia; Aldo Rizky Rahmanda (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2026)
Foreign direct investment (FDI) is widely promoted as an engine of development and is often expected to reduce income inequality through trickle-down effects, yet empirical evidence remains contested. Indonesia has actively liberalized its investment regime while income inequality has persisted at a moderate level. This study examines whether FDI inflows are associated with income inequality, measured by the Gini index, in Indonesia during 2015–2023, and draws implications for inclusive development policy. Using a quantitative panel approach, this study analyzes a balanced provincial panel of 34 Indonesian provinces over 2015–2023 (306 observations), combining the provincial Gini ratio from Statistics Indonesia (BPS) with realized foreign direct investment (FDI) by province. Panel regression was estimated and the appropriate specification selected through Chow, Hausman, and Lagrange Multiplier tests, which favored a random-effects model on log-transformed FDI. The analysis finds no statistically significant relationship between FDI and the Gini ratio (β = −0.001; p = 0.44; and R² < 0.01). A fixed-effects robustness check on the level specification yields only a small and economically negligible association. These results indicate that variation in provincial inequality is not meaningfully explained by FDI inflows over the observed period. This suggests that attracting foreign capital, by itself, does not translate into more equitable income distribution, partly because FDI in Indonesia has concentrated in capital-intensive sectors with limited labor absorption and uneven geographic distribution. The study concludes that FDI is not a primary determinant of distributional outcomes. Inequality reduction instead depends on deliberate public policy and development administration, including sectoral targeting, workforce skill development, local economic linkages, and fiscal redistribution toward lagging regions. These findings underscore the continued centrality of the state and inclusive policy design in translating investment into equitable development.